L-methionine supplementation modulates IgM+ B cell responses in rainbow trout - Martín, Diana; Ordás, M. Camino; Carvalho, Inês; Díaz-Rosales, Patricia; Nuñez-Ortiz, Noelia; Vicente-Gil, Samuel; Arrogante, Aitor; Zarza, Carlos; Machado, Marina; Costas, Benjamín; Tafalla, Carolina (Frontiers in Immunology, 2023)
The interest in dietary amino acids (AAs) as potential immunomodulators has been growing the recent years, since specific AAs are known to regulate key metabolic pathways of the immune response or increase the synthesis of some immune-related proteins. Methionine, tryptophan and lysine are among the ten essential AAs for fish, meaning that they cannot be produced endogenously and must be provided through the diet. To date, although dietary supplementation of fish with some of these AAs has been shown to have positive effects on some innate immune parameters and disease resistance, the effects that these AAs provoke on cells of the adaptive immune system remained unexplored. Hence, in the current study, we have investigated the effects of these three AAs on the functionality of rainbow trout (Oncorhynchus mykiss) IgM + B cells. For this, splenic leukocytes were isolated from untreated adult rainbow trout and incubated in culture media additionally supplemented with different doses of methionine, tryptophan or lysine in the presence or absence of the model antigen TNP-LPS (2,4,6trinitrophenyl hapten conjugated to lipopolysaccharide). The survival, IgM secreting capacity and proliferation of IgM + B cells was then studied. In the case of methionine, the phagocytic capacity of IgM + B cells was also determined. Our results demonstrate that methionine supplementation significantly increases the proliferative effects provoked by TNP-LPS and also up-regulates the number of cells secreting IgM, whereas tryptophan or lysine have either minor or even negative effects on rainbow trout IgM + B cells. This increase in the number of IgM-secreting cells in response to methionine surplus was further verified in a feeding experiment, in which the beneficial effects of methionine on the specific response to anal immunization were also confirmed. The results presented demonstrate the beneficial effects of dietary supplementation with methionine on the adaptive immune responses of fish.